A Phenomenological Study on the Removal of Administrative Tasks of Teachers at Milagros East District - Pelicano , Bobby (International Journal of Sustainability and Advanced Integrated Research, 2026)
The teaching profession in the Philippines has long been burdened with administrative tasks that detract from teachers’ primary role of facilitating student learning. In response, the Department of Education issued DepEd Order No. 002, s. 2024, mandating the removal of non-instructional duties from public school teachers to allow them to refocus on classroom instruction, professional development, and well-being. This study explores the lived experiences of secondary teachers in Milagros East District, Masbate Province, as they navigate the implementation of this policy. Guided by a phenomenological research design, the study sought to answer how teachers describe their experiences in terms of classroom instruction, professional development, and well-being; what benefits they perceive; what challenges they encounter; and what support systems they consider essential. A purposive sample of ten Junior and Senior High School teachers was selected, and data were analyzed using Braun and Clarke’s six-phase thematic analysis to ensure rigor while preserving the authenticity of teachers’ voices. Key findings revealed that teachers experienced improved instructional planning and delivery, greater participation in professional development activities, and enhanced well-being through reduced stress and better work-life balance. They also reported renewed passion for teaching and stronger learner engagement. However, challenges persisted, including managing diverse learners, limited instructional resources, and heightened expectations for innovative teaching. The study concludes that DepEd Order No. 002, s. 2024 positively impacted instructional quality, professional growth, and teacher well-being, but its sustainability depends on adequate support systems. Major recommendations include strengthening institutional support through additional staffing and resources, enhancing professional development programs, establishing monitoring mechanisms, promoting teacher wellness initiatives, and integrating technology solutions to further reduce residual workload. This research contributes localized, phenomenological evidence to the discourse on teacher workload reform, offering insights that inform policy refinement and advance SDG 4: Quality Education by empowering teachers to focus on their core instructional role.